High rate PECVD of a-C:H coatings in a hollow cathode arc plasma - Zimmermann, Burkhard; Fietzke, Fred; Klostermann, Heidrun; Munnik, Frans; Möller, Wolfhard; Lehmann, Jan (International Conference on Plasma Surface Engineering, 2013)
Amorphous carbon films deposited by plasma-based processes are of increasing importance for tribologi-cal applications, e. g. as protective coatings on components or in order to reduce their friction. However, most plasma-activated CVD and PVD techniques suffer from their poor deposition rate and low economic efficiency. At Fraunhofer FEP, a hollow cathode-based plasma source has been established as a versatile, reliable, and highly efficient tool for plasma pretreatment, plasma-enhanced PVD processes, and reactive gas activation in large volumes. As a further application field, this plasma source has been evaluated for PECVD of amorphous hydrogenated carbon films (a-C:H). Acetylene has been introduced into the hollow cathode plasma as a precursor gas. The plasma composi-tion has been characterized by an energy-resolved ion mass spectrometer. Intense ionization, dissociation, and polymerization effects have been observed, which strongly increase when the argon gas flow rate through the hollow cathode tube is reduced. Moreover, the ion energy distributions show high energy tails up to 100 eV in dependence of the spatial distribution of ion generation. a-C:H films have been deposited on stainless steel and silicon substrates with growth rates up to 1000 nm/min. Nanoindentation measurement of the a-C:H coatings reveal hardness up to 18.2 GPa. In this paper, film properties and compositions will be discussed and related to the corresponding plasma condi-tions obtained by energy-resolved ion mass spectrometry.